Indonesia As Representative Of The Global South In G20 Presidency: Return Of Global Solidarity - Yosua Saut Marulitua Gultom (Jurnal UPU, 2024)
The world is facing its biggest crisis since World War II. The COVID-19 pandemic and the Russian invasion of Ukraine have had a devastating impact on the global economy, especially on developing countries. In this context, Indonesia has played a leading role in promoting solidarity and cooperation among developing countries. The objective of this article is to explore Indonesia's role as a representative of the Global South, achieved through South-South Cooperation and its involvement in the G20, aiming to establish solidarity as a basis for post-pandemic international cooperation. The qualitative approach is utilized for this analysis. The Covid-19 pandemic has led to a rise in isolationist policies among countries in their international dealings. The Russian invasion of Ukraine further deepened divisions in global cooperation, with countries aligning either with the Western side or the Russian side, causing significant damage to trust in international cooperation. This situation is likely to disproportionately affect the Global South. Nevertheless, the article reveals that Indonesia has made efforts to promote solidarity-based international cooperation, expanding its approach from South-South Cooperation to a larger stage, the G20. Indonesia's successful 2022 G20Presidency is seen as an achievement in reinstating a degree of solidarity in international cooperation, particularly through the Bali Declaration.